Flow injection chemiluminescence determination of paracetamol - Wirat Ruengsitagoon (2018)
A simple chemiluminometric method using flow injection has been developed for the determination of paracetamol (acetaminophen), based on the chemiluminescence produced by the reduction of tris(2,2′-bipyridyl)ruthenium(III). The latter is obtained by oxidation of tris(2,2′-bipyridyl)ruthenium(II) by potassium permanganate in dilute sulphuric acid in the presence of paracetamol. A standard or sample solution was injected into the ruthenium(II) stream (flow rate 1.5 ml min-1) which was then merged with potassium permanganate in dilute sulphuric acid stream (flow rate 0.5 ml min-1). The chemiluminescence intensity is enhanced by the presence of manganese(II) ions. Under the optimum conditions, a linear calibration graph was obtained over the range of 0.3-50.0 μg ml-1and the detection limit was 0.2 μg ml-1(s/n = 3). The relative standard deviation of the proposed method calculated from 20 replicate injections of 5.0 μg ml-1paracetamol was 1.1%. The sample throughput was 90 h-1. The method was successfully applied to the determination of paracetamol in commercial pharmaceutical formulations. © 2005 Elsevier B.V. All rights reserved.